Uji Aktivitas Antikolesterol Chromolaena Odorata Secara In Silico dengan Sisi Penghambat HMG-CoA Reduktase - Irma, Tri Wahyuni; Amelia, Fitri; Rahmayani, Sherly (Departemen Kimia FMIPA UNP, 2025)
Cholesterol is a disease caused by an unhealthy lifestyle. Cholesterol occurs because fat accumulates in blood vessels so that plaques form which causes blood vessels to narrow. With this problem in mind, this research was conducted to predict drug compounds capable of treating cholesterol disease by comparing them with simvastatin. Chromolaena odorata can be used as a medicinal plant that can treat cholesterol disease because this plant contains active compounds of flavonoids. This research tries to see the active interaction with HMG-CoA reductase inhibition in an improved way using Moe 2009.10 software. Based on the results of research that has been done based on the comparison of ∆G, compound O-Geranylvanillin, Avenestergenin B2, 5-O-Methylembelin, Kaempferol 3-[2’’-(6’’’-coumaroylglucosyl)- rhamnoside] 7-glucoside, ( ± )-Taxifolin, Hesperetin, ( ± )-Naringenin, Luteolin, 3′ ,4′ -Methylenedioxy epicatechin 5,7-dimethyl ether has the potential to be used as a candidate for anti-cholesterol drugs to replace simvastatin through the HMG-CoA reductase inhibition mechanism.